Oesophageal cancer : association with visceral obesity, inflammation and optimisation of postoperative outcomes - Doyle, Suzanne (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Surgery, 2013)
The incidence of oesophageal cancer is rising in the developed world and has paralleled the rising prevalence of obesity. This is an aggressive malignancy with poor overall survival rates. Thus there is an impetus to identify mechanisms driving this increase in oesophageal cancer incidence and strategies to improve outcomes in patients receiving treatment. The aim of this thesis was to investigate further the relationship between visceral obesity and oesophageal cancer, in terms of both tumour biology and postoperative outcomes. In addition, the potential role of immuno-nutrition with eicosapentaenoic acid in improving postoperative outcomes in oesophagectomy patients was assessed.
Keywords: Surgery, Ph.D.; Ph.D. Trinity College Dublin.